Dā’ish vs Tanẓīm Al-Dawlah: BREAK Analysis of The Names of ISIS in Arab Mass Media - Reflinaldi Reflinaldi; Sawirman Sawirman; Fajri Usman (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
This study aims to analyze the meaning of ISIS names in the Arab mass media from the BREAK theory perspective. The research data were taken from two Syrian mass media: Tishrīn and ‘Inab Baladī. The name Dā’ish is used as the primary discourse, while the name Dā’ish is a secondary discourse. The data was collected by observing the basic technique of tapping and the advanced technique of note-taking. Data analysis was carried out using identity method. The findings show that the meaning of primary discourse is structured through the eclectic use of theory on aspects of sound, form, meaning construction, and meaning changes. The analysis found that primary discourse has a negative meaning tendency and is contrary to religion's moral values (Islam) and state. Meanwhile, the meaning of secondary discourse is carried out by combining the theory of nominal groups, word structures, nominal relations, and stylistics. Secondary discourse has an ambiguous meaning because it represents ISIS as an entity that can be understood in two domains at once: organization and state. The comprehensive analysis of BREAK has shown clear linguistic stages of meaning so the meaning of ISIS names can be clearly understood. Â